Associação entre polimorfismos em enzimas de reparo de DNA e ocorrência de meningite bacteriana. - Silva, Thayse Azevedo da (2008)
Despite advances in vaccine development and therapy, bacterial meningitis (BM) remains a major cause of death and long-term neurological disabilities. As part of the host inflammatory response to the invading pathogen, factors such as reactive oxygen species are generated, which may damage DNA and trigger the overactivation of DNA repair mechanisms. It is conceivable that the individual susceptibility and outcome of BM may be in part determined by non synonymous polymorphisms that may alter the function of crucial BER DNA repair enzymes as PARP-1, OGG-1 and APE-1. These enzymes, in addition to their important DNA repair function, also perform role of inflammatory regulators. In this work was investigated the non synonymous SNPs APE-1 Asn148Glu, OGG-1 Ser326Cys,PARP-1 Val762Ala, PARP-1 Pro882Leu and PARP-1 Cys908Tyr in patients with bacterial meningitis (BM), chronic meningitis (CM), aseptic meningitis (AM) and not infected (controls). As results we found increased frequency of variant alleles of PARP-1 Val762Ala (P = 0.005) and APE-1 Asn148Glu (P=0.018) in BM patients, APE-1 Asn148Glu in AM patients (P = 0.012) and decrease in the frequency of the variant allele OGG-1 Ser326Cys in patients with CM (P = 0.013), regarding the allelic frequencies in the controls. A major incidence of individuals heterozygous and/ or polymorphic homozygous in BM for PARP-1 Val762Ala (P= 0.0399, OD 4.2, 95% IC 1.213 -14.545) and PARP-1 Val762Ala/ APE-1 Asn148Glu (P = 0.0238, OD 11.111, 95% IC 1.274 - 96.914) was observed related to what was expected in a not infected population. It was also observed a major incidence of combined SNPs in the BM patients compared with the control group (P=0.0281), giving evidences that SNPs can cause some susceptibility to the disease. This combined effect of SNPs seems to regulate the principal cytokines and other factors related to BM inflammatory response and point the importance of DNA repair not only to repair activity when DNA is damaged, but to others essential functions to human organism balance.